Stimulating training and access to HIV research experiences (STAR program): a protocol for a crowdsourced, project-based, implementation science training program using mixed-methods design - Iwelunmor, Juliet; Thurston, Idia; Airhihenbuwa, Collins; Tang, Weiming; Nwaozuru, Ucheoma Catherine; Anikamadu, Onyekachukwu; Oladele, David; Takenaka, Bryce; Ameen, Khadijah; Olusanya, Olufunto A.; Ojo, Temitope; Tucker, Joseph D. (Frontiers in Public Health, 2025)
BackgroundHIV is more common among underrepresented minority adolescents and young adults (AYA, 13–24 years old) in the United States. Low uptake of HIV prevention services suggests a missed opportunity for implementing evidence-based interventions such as pre-exposure prophylaxis (PrEP) and sexually transmitted infection testing among this important population. Most research institutions in the United States also have limited opportunities for AYA training, mentorship, and capacity-building activities.MethodsThe “Stimulating Training and Access to HIV Research Experiences” (STAR) program brings together a highly qualified group of research mentors to achieve three specific aims: (1) identify and recruit underrepresented minority AYA interested in HIV research for STAR using crowdsourcing; (2) develop implementation science research and project-based design capacity for underrepresented trainees at participating US institutions; and (3) initiate and sustain enduring AYA research capacity through a digital participatory learning community. A three-stage approach is taken to increase the number of racial and ethnic minority trainees that: (1) learn about HIV prevention services; (2) lead the design of HIV prevention services; and (3) launch and evaluate HIV prevention services serving UREM AYAs at participating community sites. Furthermore, we create a Participatory Learning Community (PLC), with virtual opportunities for interaction, mentoring, and sharing of project-based designs so that rapid exchanges can occur and be documented among trainees, faculty, and invited scholars in the field.DiscussionThere is a substantial unmet need for adolescent and young adult (AYA) HIV implementation research training in the United States among underrepresented minority AYAs. STAR seeks to identify highly qualified trainees through open calls, build capacity for youth-led research using designathons and innovation bootcamps, and sustain these benefits through participatory learning communities. These approaches break new ground in HIV training using participatory methods that empower AYAs to become junior leaders while building institutional capacity for AYA HIV research.